WORKSHOP DAN KOMPETISI ROBLOX STUDIO DENGAN AI UNTUK SMA/SMK DI JAKARTA DAN SEKITARNYA - Darius Andana Haris; Ivander; Amita Ratu Osswald; Deven Yudino (Jurnal Serina Abdimas, 2025)
The Roblox Studio Workshop and Competition with AI is a commUnity service activity conducted by the Game Development Lab of the Faculty of Information Technology, Tarumanagara University. The target group of this activity is high school/vocational school students in Jakarta and its surrounding areas. This activity was carried out over two days. The first day was an introduction and training in game Development with an AI approach in Roblox Studio, while the second day was a competition for presentations of work and the determination of winners. In the training session, participants received a basic explanation of Roblox Studio, world design techniques, and how Artificial Intelligence can be applied to support interactions and mechanisms in games. With a hands-on approach, students not only learned theory but also implemented their knowledge in the form of simple projects. For the competition, each team created a metaverse world with the theme "Learning" using Roblox Studio. Their work was assessed by a panel of judges from the collaboration partner, namely AKA Virtual, with consideration of the following aspects: Environment (35%), interactivity (30%), and presentation (35%). This competition was group competition with a maximum of three people per team. Each high school/vocational school could send a maximum of two student teams and be accompanied by one supervising teacher. The activity was held in the FTI UNTAR computer laboratory, which is equipped with adequate facilities to support the training and competition process. The benefits of this activity are diverse. In addition to introducing the concept of Artificial Intelligence and game Development through the Roblox platform, this activity also serves as a means to develop students' soft skills, such as teamwork, problem-solving, and creativity. Furthermore, this activity is expected to bridge high school and vocational school students to learn more about the Faculty of Information Technology at Tarumanagara University, while also motivating them to continue their studies in technology and game Development. Workshop dan kompetisi Roblox Studio dengan AI merupakan kegiatan pengabdian kepada masyarakat yang dilaksanakan oleh Lab Game Development dari Fakultas Teknologi Informasi Universitas Tarumanagara. Sasaran dari kegiatan tersebut yaitu siswa SMA/SMK di wilayah Jakarta dan sekitarnya. Kegiatan ini telah dilaksanakan dalam waktu 2 hari. Hari pertama berupa pengenalan dan pelatihan pengembangan game dengan pendekatan AI di Roblox Studio, sementara hari kedua merupakan kompetisi presentasi karya dan penentuan pemenang. Pada sesi pelatihan, peserta mendapatkan penjelasan dasar mengenai Roblox Studio, teknik desain world, serta bagaimana Artificial Intelligence dapat diterapkan untuk mendukung interaksi maupun mekanisme dalam game. Dengan pendekatan praktik langsung, siswa tidak hanya belajar teori, tetapi juga mengimplementasikan pengetahuan mereka dalam bentuk project sederhana. Untuk kompetisi, setiap tim membuat world metaverse bertema "Belajar" menggunakan Roblox Studio. Hasil karya mereka dinilai oleh tim juri yang berasal dari mitra kerja sama, yaitu AKA Virtual, dengan memperhatikan aspek: Environment (35%), interaktivitas (30%), dan presentasi (35%). Kompetisi ini bersifat kelompok dengan maksimal tiga orang per tim. Setiap sekolah SMA/SMK dapat mengirimkan maksimal dua tim siswa dan didampingi oleh satu guru pembimbing. Kegiatan diselenggarakan di laboratorium komputer FTI UNTAR yang telah dilengkapi fasilitas memadai untuk mendukung proses pelatihan dan kompetisi. Manfaat kegiatan ini sangat beragam. Selain mengenalkan konsep Artificial Intelligence dan pengembangan game melalui platform Roblox, kegiatan ini juga menjadi sarana pengembangan soft skill siswa, seperti kerja sama tim, problem solving, dan kreativitas. Lebih jauh, kegiatan ini diharapkan dapat menjadi jembatan bagi siswa SMA/SMK untuk mengenal lebih dekat Fakultas Teknologi Informasi Universitas Tarumanagara, sekaligus memotivasi mereka agar tertarik melanjutkan studi di bidang teknologi dan game Development.